Optimization and purification of natural protein extract from hazelnut press cake and its antioxidant activity - Fang, Yuan; Li, Jiajie; Zhu, Xuyao; Li, Xinru; Xu, Songzhe; Wu, Hao; Zhang, Huifeng; Luo, Yanan (Frontiers in Nutrition, 2025)
This study aimed to enhance the basic criteria for protein extraction from hazelnuts via the response surface technique and to explore the antioxidant characteristics of the isolated hazelnut protein. The purified hazelnut protein with high quality was obtained using the ÄKTA pure system through a HiTrap DEAE FF column. The refined parameters for extraction included: an extraction duration of 2 h, a temperature set at 33 °C, a liquid-to-solid ratio 8:1, and a 2.32 g protein extraction yield/50 g hazelnut press cake. The crude hazelnut protein was identified by LC-MS, which primarily included 41 proteins (only 10 shown). Antioxidant-activity investigations revealed that purified hazelnut protein had high scavenging activity of DPPH radicals. Furthermore, H2O2-induced cell oxidative damage was reduced by increasing cell viability and reducing ROS levels. The basis for purified hazelnut protein extraction was also explored. Our findings showed that hazelnut protein may be a promising natural antioxidant.